Interactions between eye movements and posture in children with neurodevelopmental disorders. Issue 71 (December 2018) - Bucci, Maria Pia; Goulème, Nathalie; Dehouck, Delphine; Stordeur, Coline; Acquaviva, Eric; Septier, Mathilde; Lefebvre, Aline; Gerard, Christophe-Loïc; Peyre, Hugo; Delorme, Richard
Highlights: Eye movement's parameters were differently affected by postural conditions. The quality of fixation was weak in children with neurodevelopmental disorders with respect to typically developmental children. Postural stability was poor in children with neurodevelopmental disorders with respect to typically developing children. Abstract: In everyday life, our activities frequently involve the simultaneous performance of two or more tasks. Sharing attention between two concurrent tasks may result in a decrease in performance specifically among children with neurodevelopmental disorders. The objective of the study was to determine whether the influence of postural conditions (sitting condition, single task; standing condition, dual task) on eye movement performances on three visual tasks with high attentional load (visually-guided saccade task, memory-guided saccade task and fixation task) was different in children with neurodevelopmental disorders (attention deficit and hyperactive disorder, dyslexia, and high functioning autism spectrum disorder) when compared to typically developing children. One hundred and four children (26 per group, sex-age- and IQ-matched groups) were evaluated. We found that for the fixation task only, the three groups of children with neurodevelopmental disorders had poorer eye movements performances in the standing condition compared to the sitting condition while no such difference was found for typically developing children. We suggest that children with neurodevelopmental disorders have fewer attentional resources available for performing correctly oculomotor tasks with high attentional load leading to impairment of these tasks for maintaining a good level of postural stability.